Food Security and Frozen Protein Consumption: A Comprehensive Analysis of Determinants, Perceptions, and Policy Implications in Eastern Indonesia's Remote Region - Thedjokusuma, Richard; Wajo, Mohamad Jen; Mulyadi, Mulyadi; Hartini, Sri (Jurnal Sain Peternakan Indonesia, 2026)
Remote regions of Eastern Indonesia face complex food security challenges, particularly in accessing sustainable protein. Frozen chicken has emerged as a potential solution, yet comprehensive analyses of its multi-dimensional role in household food security systems are scarce. This study employs an integrated mixed-methods approach to examine the socio-economic, perceptual, and behavioral determinants of frozen chicken consumption and its implications for food security policy.  A cross-sectional survey (n=131) was complemented with in-depth interviews (n=25) and focus group discussions (n=4) in Fakfak Regency. Advanced statistical analyses, including structural equation modeling (SEM) and cluster analysis, were employed to identify complex relationships and consumer segments. SEM revealed that consumption behavior was directly influenced by perceived quality (β=0.42, p<0.001), accessibility (β=0.38, p<0.001), and price fairness (β=0.29, p=0.003). Cluster analysis identified four distinct consumer segments: "Practical Adopters" (34.4%), "Quality-Sensitive Consumers" (28.2%), "Price-Driven Users" (22.9%), and "Reluctant Acceptors" (14.5%). Qualitative analysis uncovered nuanced perceptions of frozen chicken as both a "lifeline" during shortages and a "compromise" when fresh options are unavailable. Frozen chicken serves as a strategic buffer for food security, but complex consumer perceptions and market dynamics moderate its effectiveness. Policy interventions require segment-specific approaches addressing quality assurance, supply chain reliability, and consumer education.